First person singular : stories - Murakami, Haruki, 1949- (Alfred A. Knopf, 2021)
"A riveting new collection of short stories from the beloved, internationally acclaimed, Haruki Murakami. The eight masterful stories in this new collection are all told in the first person by a classic Murakami narrator: a lonely man. Some of them (like "With the Beatles," "Cream," and "On a Stone Pillow" ) are nostalgic looks back at youth. Others are set in adulthood--"Charlie Parker Plays Bossa Nova," "Carnaval," "Confessions of a Shinagawa Monkey" and the stunning title story. Occasionally, a narrator who may or may not be Haruki himself is present, as in "The Yakult Swallows Poetry Collection." Is it memoir or fiction? The reader decides. The stories all touch beautifully on love and loss, childhood and death . . . all with a signature Murakami twist"--